Patient Referrals in Dangme-West District: Patient and Service Providers Perspective - Asare, P.K. (University of Ghana, 2002)
Patients’ referral is an integral part of health care delivery in the district of study. The Dangme-West District with relies on satellites of referral hospitals outside the district for care of patients referred from the districts. With the introduction of community based health insurance scheme, the linkage with these referral hospitals has seen the greatest challenges. A lot of effort and negotiations had to be put in place to make it possible for the referred patients from the district to be managed at these referral hospitals. Besides the physical access, the travel cost and other challenges on patient referral, there is growing dissatisfaction among referred patients on referral process, which may have negative effect on participation in the health insurance scheme in the district. The main objective of the study was to assess the perceptions and attitude of referred patients and health service providers on patient referrals in the district and also identify the various factors affecting patient referral in the district. The study was a descriptive cross-sectional study involving referred patients and health service providers. One hundred and eighty eight referred patients and forty-two health service providers were interviewed using questionnaires. Focus group discussions were carried for the referred patients and in-depth interviews were conducted on service providers. Review of available records on referred patients with a checklist was also carried. Fifty five percent of the referred patients interviewed were registered in the community health insurance scheme in the district. The patient referral rate from the primary health care facilities to the referral hospitals was eight per thousand patients (0.8%) for the period under study. Ninety percent of the patient referrals were for treatment and operation whilst ten percent of these referrals were for various investigations. 72% of referred patients were given referral notes and only 15% of referred patients were given referral feedback note to the referring primary health facilities. The average travel time to these referral hospitals was 1-2 hours. From the perspective of these referred patients, the attitude of health staff at these referral hospitals was cordial except 13% of them who were unhappy with the service providers’ attitude. The referred patients experienced less waiting time at the referral hospitals. 7% of the referred patients were transported to the referral hospitals by an ambulance whilst 93% used commercial transport. Review of the existing records on patient referral at the referral hospitals showed that none of these referral hospitals had a record of patient referral in outpatient department registers. At the primary referring health facilities 75% of them had records on patients’ referral in the outpatient department registers. The insured patients were properly referred with referral notes than non-insured patients. Patient referrals form level A to level B health facilities were delayed especially referrals from Traditional Birth Attendants and the reasons for such delays were lack of skills of these health practitioners. Reasons for the delay of patient referrals from level B health facilities to referral hospitals were long distance travelled to these hospitals. The identified factors that have an impact on referral process in the district include physical access of referral hospitals, longer travelling time, inadequate referral records, weak inter-facility communication, referral delays and staff attitude. The following recommendations are suggested, improve referral records and inter-facility communication, education of service providers on timely referrals, provision of designated transport like ambulance for sub-districts and also involvement of private transport owners in the referral process. Good patient information and cordial relationship between service providers and patients should be encouraged. Upgrading of health centre to referral hospital in the district is recommended to reduce the travel time and cost to referred patients. Expansion of the health insurance coverage is also recommended. Besides the financial access, the insured patients are properly referred and records on such patients are accurate.